E-055 Incidence of External Ventricular Drainage Placement on Rebleeding of Ventricular Arteriovenous Malformations. (26th July 2014) - Robert, T; Blanc, R; Gilboa, B; Ciccio, G; Fahed, R; Redjem, H; Pistocchi, S; Bartolini, B; Piotin, M
Abstract : Background: Intraventricular arteriovenous malformation (AVM) is an exceptional but well recognised source of intraventricular haemorrhage. The impact of external ventricular drainage (EVD) for acute hydrocephalus on AVM rebleeding has not been yet reported in the literature. Methods: Since 1995, clinical and angiographic data of cerebral AVMs were prospectively collected. In this study, we selected patients harbouring an AVM located in a lateral ventricle discovered by a bleeding. The implication of following factors on rebleeding was analyzed: age, sex, associated aneurysm, nidus size and type, venous ectasia, Spetzler-Martin grade, placement of EVD and side of the drainage. Results: Twenty-two patients (mean age 27.9 years) were consecutively treated. Locations of the AVM included the atrium in 13 cases (59.1%), the frontal horn in 12 cases (54.6%) and the occipital horn in 2 cases (9.1%). 9 AVMs (40.9%) interested eloquent areas. The Spetzler-Martin grade was II in 10 cases (45.5%), III in 3 (13.6%), IV in 8 (36.4%) and V in 1 case (4.5%). Associated aneurysms were classified as nidal (2 cases, 9.1%), flow-related (2 cases, 9.1%) and unrelated to the AVM (3 cases, 13.6%). Ten (45.5%) patients developed a secondary hydrocephalus. Five EVD were placed in the ventricle of the AVM and the five other in the contralateral ventricle. The placement of the shunt in the contralateral ventricle was a significant risk factor AVM rebleeding (95% CI: 4.33–10.42, p < 0.005). The presence of an associated aneurysm, diffuse type of the nidus and the placement of EVD seemed to be risk factors for the rebleeding of the AVM. Conclusions: The placement of EVD in the opposite side of the AVM significantly increased the risk of rebleeding of the AVM. We recommend the placement of EVD in the side of the AVM even if the obturation of the shunt could be problematic also as the avoidance of the nidus by the catheter. Disclosures: T. Robert: None. R. Blanc: None. B. Gilboa: None. G. Ciccio: None. R. Fahed: None. H. Redjem: None. S. Pistocchi: None. B. Bartolini: None. M. Piotin: None.